The performance of unit trust fund in Malaysia / Nur Nadhirah Sabar - Sabar, Nur Nadhirah (Faculty of Business Management, 2017)
This paper is to identify the performance of unit trust funds in relation to the return on investment and the risk free rate of the portfolio. According to the earlier studies shows that unit trust do not outperform the market as well as the manager‟s ability to beat the market (Sharpe, 1996; Jensen 1968; Firth, 1977). Thus, the evidence shows indirectly that the market is strangely efficient and yet the studying of past stock prices still not supporting in the prediction of future price movements. The objective of this study is to examine the performance measure of return in unit trust funds in relation to the market return and to determine the factors affecting the performance return of unit trust funds for investor‟s decision making process. Furthermore the research paper will be using market price as net assets value as dependent variable and the independent variables is the performance return measure as Treynor Ratio, Jensen‟s Alpha and Sharpe Ratio as a model to measure the performance. This research study more focused on using the secondary data collected by using Fundsupermart, Morningstar, Finance Yahoo, Bursa Malaysia and Federation of Investment Managers Malaysia (FiMM). The study is conducted starting from the period of 2013 until 2015 on monthly basis. There are four companies selected in this study which are Cimb Berhad, Eastspring Investment, RHB Bank Berhad and Affin Hwang Investment Bank Berhad. Based on the four companies there are eight unit trust funda are selected. Besides that, Statistical method will be used in this study by using panel least square to test the relationship between the dependent variable and independent variables. Thus, descriptive analysis, unit root test, regressions analysis and heteroskedasticity – white test were used in the analysis. By using E-views program the data can be easily analyze for the interpretation of results.